Dependencia emocional y su repercusión en la salud mental en un joven de 17 años de la ciudad de Babahoyo - Guevara Valle, Odalis Michelle (2023)
Emotional dependence is the pathological need to feel recognized and accepted by another person, this during adolescence greatly influences mental health, causing the appearance of behavioral and emotional disorders such as depression or stress, or even the development of personality disorders such as dependent personality disorder, borderline personality disorder, or obsessive compulsive disorders. The case study presents as a study topic "Emotional dependence and its impact on mental health in a 17-year-old boy from the city of Babahoyo" which aims to determine how emotional dependence influences the mental health of the patient. , for this it was necessary to implement information collection techniques such as clinical interview, clinical observation, clinical history, in addition to the application of psychological instruments such as BDI II, MMPI 2, CDE, used to clarify the clinical hypothesis about the observed behavior, and the results of the techniques and instruments resulting in the diagnosis of F32.0 Moderate depressive episode, in conclusion the objective was achieved and to be able to help his patient to improve his quality of life.